Relationship between Wound Severity, Discomfort, and Psychological Problems in Patients with a Diabetic Foot Ulcer in Indonesia: A Cross-sectional Study - Dewi Gayatri; Elly Nurachmah; Muchtaruddin Mansyur; Pradana Soewondo; Suriadi Suriadi (Universidad de La Sabana, 2020)
Relación entre la gravedad de la herida, la molestia y los problemas psicológicos en pacientes con úlcera del pie diabético en Indonesia: estudio transversal Relação entre gravidade da ferida, desconforto e problemas psicológicos em pacientes com úlcera diabética do pé na Indonésia: um estudo transversal Objectives: The purpose of this study is to identify the relationship between wound severity, discomfort, and psychological problems in patients with a diabetic foot ulcer in Indonesia. Methods: A cross-sectional study is conducted in three general hospitals and one clinic in Indonesia. The Bates-Jensen wound assessment tool (BWAT), the discomfort evaluation of wound instrument (DEWI), and the depression, anxiety, and stress scale (DASS) are used to measure the variables of interest. Path analysis is performed to evaluate the association between wound severity, discomfort, and psychological problems. Results: Of 140 patients with diabetic foot ulcers who joined this study, the majority experienced immobilization (74.3 %), pain (69.3 %), and sleep disturbance (63.6 %). The means were as follows: discomfort (2.35 ± 0.33), depression (1.34 ± 0.41), stress (1.49 ± 0.48), anxiety (1.43 ± 0.40), and wound severity (31.35 ± 9.96). Discomfort partially mediated the relationship between wound severity and psychological problems, which indirect effect was 0.11. Conclusion: High prevalence of discomfort, both physical and psychological, was found in patients with a diabetic foot ulcer. Discomfort mediates the relationship between wound severity and psychological problems. Integrating comfort into wound care management may help to reduce the psychological burden. Para citar este artículo / To reference this article / Para citar este artigo Gayarti D, Nurachmah E, Mansyur M, Soewondo P, Suriadi S. Relationship between Wound Severity, Discomfort, and Psychological Problems in Patients with a Diabetic Foot Ulcer in Indonesia: A Cross-sectional Study. Aquichan. 2020;20(3):e2033. DOI: https://doi.org/10.5294/aqui.2020.20.3.3 Recibido: 02/09/2019 Aceptado: 13/07/2020 Publicado: 07/09/2020